A BDNF-TrkB autocrine loop enhances senescent cell viability - Anerillas, Carlos; Herman, Allison B.; Munk, Rachel; Garrido, Amanda; Lam, Kwan-Wood Gabriel; Payea, Matthew J.; Rossi, Martina; Tsitsipatis, Dimitrios; Martindale, Jennifer L.; Piao, Yulan; Mazan-Mamczarz, Krystyna; Fan, Jinshui; et al. (Nature communications, 2022)
Cellular senescence is characterized by cell cycle arrest, resistance to apoptosis, and a senescence-associated secretory phenotype (SASP) whereby cells secrete pro-inflammatory and tissue-remodeling factors. Given that the SASP exacerbates age-associated pathologies, some aging interventions aim at selectively eliminating senescent cells. In this study, a drug library screen uncovered TrkB (NTRK2) inhibitors capable of triggering apoptosis of several senescent, but not proliferating, human cells. Senescent cells expressed high levels of TrkB, which supported senescent cell viability, and secreted the TrkB ligand BDNF. The reduced viability of senescent cells after ablating BDNF signaling suggested an autocrine function for TrkB and BDNF, which activated ERK5 and elevated BCL2L2 levels, favoring senescent cell survival. Treatment with TrkB inhibitors reduced the accumulation of senescent cells in aged mouse organs. We propose that the activation of TrkB by SASP factor BDNF promotes cell survival and could be exploited therapeutically to reduce the senescent-cell burden. Selective elimination of senescent cells is an approach that has shown promise to ameliorate age-associated pathologies in preclinical models. Here the authors report that BDNF enhances senescent cell viability via TrkB in cultured cells, and that TrkB inhibition can reduce the accumulation of senescent cells in aged mouse organs.